Daily Activity And Microhabitat Preference of Sambar Deer (Cervus Unicolor Kerr, 1792) In The University of Lampung Sanctuary - Gusmasari, Nefi; Rustiati, Elly L (Universitas Jambi, 2008)
The study to learn the daily activity and microhabitat preference of sambar deer was conducted in theUniversity of Lampung Sanctuary by scanning method. The general condition of the sanctuary was observed by rapidassessment method, vegetation registration was noted by one meter-quadrant. The highest daily activity proportionwere feeding (45.8%), followed by sleeping (30.6%) and resting (23.7%) respectively. Sambar microhabitatpreferences included Imperata- bushed areas for sleeping and resting activities and areas with grasses, shrubs andtrees for feeding activity.